Treatment and Operating Cost Analysis of Textile Wastewater by Electro-coagulation Using Mild Steel Electrodes - Paul, Kalpataru; Ashik-Un-Noor, Shaikh; Jalil, M. A. (International Journal of Bio-resource and Stress Management, 2019)
Conventional treatment of industrial wastewater is often ineffective in removing color, especially from highly colored textile wastewater. This research was undertaken to investigate the removal of color and COD from textile effluent using electro-coagulation process. The effects of applied current flow, different types of electrodes, age of wastewater, EC time and initial pH on the removal of color and COD were studied. Cost estimation was also been assessed. Aluminium, mild steel and stainless steel plates were used as electrodes and comparison among these plates regarding the removal efficiencies assessed. Wastewater from two different textile industries were collected four times and treated in the laboratory. Under the experimental conditions, color removal up to 98%, COD removal up to 67% and turbidity removal up to 71.5% were achieved. The results suggest that electrocoagulation process is very effective for removal of color. It was observed that slightly low pH than initial would be effective for color and COD removal and low electricity cost. Considering economical and effectiveness of the treatment process the initial pH should be lowered about 1.6-2 than the raw sample. It was also observed that the removal of color was more effective when the experimental run using fresh sample rather than old sample. As metal decomposes in this process; mild steel was found to be more economical than aluminium. The operating cost includes the energy cost of EC and the material cost. Operating cost as 0.53 US $/m3 at 5 ampere and 15 min EC time was evaluated.